Starved Guts: Morphologic and Functional Intestinal Changes in Malnutrition. Issue 5 (November 2017) - Attia, Suzanna; Feenstra, Marjon; Swain, Nathan; Cuesta, Melina; Bandsma, Robert H.J.
Abstract : ABSTRACT: Malnutrition contributes significantly to death and illness worldwide and especially to the deaths of children younger than 5 years. The relation between intestinal changes in malnutrition and morbidity and mortality has not been well characterized; however, recent research indicates that the functional and morphologic changes of the intestine secondary to malnutrition itself contribute significantly to these negative clinical outcomes and may be potent targets of intervention. The aim of this review was to summarize current knowledge of experimental and clinically observed changes in the intestine from malnutrition preclinical models and human studies. Limited clinical studies have shown villous blunting, intestinal inflammation, and changes in the intestinal microbiome of malnourished children. In addition to these findings, experimental data using various animal models of malnutrition have found evidence of increased intestinal permeability, upregulated intestinal inflammation, and loss of goblet cells. More mechanistic studies are urgently needed to improve our understanding of malnutrition-related intestinal dysfunction and to identify potential novel targets for intervention.